1990
DOI: 10.1177/00220345900690061401
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopic Characterization of Hypersensitive Human Radicular Dentin

Abstract: Transmission electron microscopy (TEM) and x-ray microanalysis (XMA) were used for the study of the ultrastructure of the lumens of dentinal tubules in superficial layers of dentin specimens obtained by use of a new biopsy technique from both hypersensitive and naturally desensitized areas of exposed root surfaces, in vivo. The TEM images showed clearly that the lumens of most of the tubules were occluded with mineral crystals in naturally desensitized areas, but such lumens were empty and surrounded with peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
14

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 11 publications
1
50
1
14
Order By: Relevance
“…Moreover, the Ca/P ratios in PTD and in ITD compared between the species were statistically insignificant. Similar results were reported in human dentin by Yoshiyama and co-workers [43] and in equine dentin by Kodaka's research group [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the Ca/P ratios in PTD and in ITD compared between the species were statistically insignificant. Similar results were reported in human dentin by Yoshiyama and co-workers [43] and in equine dentin by Kodaka's research group [25].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the great similarity in microstructural and chemical composition of porcine and human dentin points to suitability of porcine dentin use in human dental research. Indeed, no significant difference is found between the bond strength of human and porcine dentin to a number of resin cements [43], and a similar outcome is reported after etching of either of dentin, porcine and human [44].…”
Section: Discussionmentioning
confidence: 57%
“…Common histological findings are enlarged dentinal tubules that occur in areas with larger numbers of tubules per area, when compared with dentin without sensitivity [9,10]. Symptom management ranges from the use of over the counter products (OTC) containing active ingredients that either desensitize the nerve tissue at the base of the dentin tubule or by encouraging the promotion of dentin tubule occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental analysis has also been used in this case to evaluate the degree of substitution within bioapatite by quantifying the ratio between two elements using EELS, or often EDX [21][22][23]. For example, in an EDX study of mineralised dental tissues by Srot et al [21], peritubular dentine was found to contain a significantly lower Ca/P ratio (and higher and variable Mg/P) compared to intertubular dentine, which was taken as evidence that magnesium partially substitutes for calcium in the mineral.…”
Section: Substitutions In the Mineral Phasementioning
confidence: 99%